HUBUNGAN ADVERSITY QUOTIENT DENGAN KEMAMPUAN PEMECAHAN MASALAH SISWA SMP PADA PEMBELAJARAN MATEMATIKA - Lisa Dwi Afri (State Islamic University of North Sumatra, 2018)
Problem solving must be developed and internalized in mathematicslearning, so students have problem solving skills that students cantransfer to their daily lives when facing problems or difficulties.There is a mental attitude that affects a person's success to become asuccessful problem solver, namely adversity quotient. This mentalattitude affects the mindset and emotions so it is not easy to give upin solving problems. This study aims to measure the relationshipbetween adversity quotient and problem solving abilities of juniorhigh school students in mathematics learning. This research is acorrelation study. The population was students of SMPN 1 PadangPanjang 2014/2015 academic year, while 32 samples were selectedby purposive sampling. The data was collected using an adversityquotient scale and a mathematical problem solving ability test. Datawere analyzed by regression correlation techniques. The results ofdata analysis showed a correlation coefficient between adversityquotient variables with mathematical problem solving abilities of r =0.756> rtable (0.297), meaning that there was a significant positiverelationship between adversity quotient and mathematical problemsolving abilities. The coefficient of determination obtained is r2 =0.572 indicating that adversity quotient has an effect of 57.2% onmathematical problem solving abilities of junior high schoolstudents, while 42.8% is influenced by other factors